Development of a Pipe Leakage Detection with Simulated Acoustic Model for Water Distribution System - Arowolo, M. O.; Adekunle, A. A.; Olaniyan, O. M.; Fadiji, E. A.; Oginni, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The paper presents a method for detecting pipe leakage in a water distribution system using a simulated acoustic model. The study utilized Particle Swarm Optimization (PSO) to determine the optimal position for the leakage point in relation to the sensors. The objective function was created, and time delays were optimized using PSO simulated via MATLAB. The analysis focused on examining both vertical and horizontal flow configurations. The system was calibrated, data was extracted, and it was utilized for leakage automation. The study found that the optimal leakage point is 10.12 cm, measured to the left sensor1 in the horizontal configuration with a 0.02 second time delay. The second leakage point in the horizontal configuration has a time delay of 0.05 seconds, while the third point has a delay of 0.08 seconds. Eight false alarm frequencies were detected in the water flow and no leakage mode, with 100% of the false alarms indicating no flow or leakage. The system false alarm disappears when the system is pressurized for a long period of time. The study demonstrates the importance of detecting pipe leakage in water distribution systems using a simulated acoustic model in rural areas, developing countries, and small and medium-sized industries.